What Do You Mean By a Solution to an Operator Equation? - Sarkar, T.K. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The main thrust of this presentation is to illustrate that for many electromagnetic field problems the quality of the solution is very subjective and not objective at all. Therefore to classify solutions on a subjective criteria which is not scientific will create more problems than it would solve. The underlying feature to all this is what do "we mean" by a solution.